Prevalencia del Helicobacter pylori mediante Elisa en estudiantes de la Facultad de Odontología de la Universidad de San Marcos - Moromí N., Hilda (2002)
With the objective of prove the prevalence of the Helicobacter pylori (flp) in odontology students and establish the relation between the positive seroreactors and related symptomatologies to Hp, like: stress, gastritis, ulcer and cancer it was selected a random population sample of 91 students between 15-24 years old, for the detection of IgG antibodies in sera using the Kit Platelia R. To the same population sample ¡t was applied a personal information form lo be filled by the students. Front a total of 91 students that have finished the study, ¡t was founded a general seroprevalence of the Hp in 72,5 % (66/91), with sexual prevalence of 68,3 and 76 %, in women and men, respectively. At the time of relate the personal information, with the positive seroreactors, it was founded that: the 73,1 % (19/26) have stress, 61,5 % (8/13) have gastritis y 100 % (2/2) have ulcer. With regard to the symptomatologies in the student of the sample, it was founded that: the 28,6 % (26/91) have stress, 14,3 % (13/91) have gastritis y 2,2 % (2/91) have ulcer In relation of the symptomatologies in the students familiars, ¡t was founded that the 33 % (30/91) have gastritis, 18,7 % (17/91) have ulcer and a 5,5 % (5/91) have cancer It was concluded that the 72,5 % of the de positive seroreactors are between the rank of Hp seroprevalence of the countries in development; that there is a high relation (> 60 %) of ~ositive seroreactors with registered symptomatologies in the forms, like: stress, gastritis and ulcer; in the same manner it reveal sequestered numbers of the presence of these symptomatologies in the students, and these in relation with their familiars, nevertheless, the applied statistic test do not found significatives differences.